O estudante de medicina da Unifenas-BH, a especialização médica e o mercado de trabalho - Mendonça, Fernando Luiz de (2018)
Introduction: The choice of a medical specialty and knowledge of the labor market are essential items for professional successfulness and the good functioning of the health services. Objective: To investigate the factors that influence the choice of specialty and the apprentice expectations on the issues that involve the effectiveness of practicing medicine and the labor market. Methodology: Standardized questionnaires on factors related to the choice of medical specialty were applied to medical students from the 9th to 12th periods at Jose do Rosario Vellano University – UNIFENAS, Campus Belo Horizonte. Results: 179 questionnaires were given, predominantly women (64.8%). Participants are from all regions of the country. 84.1% completed high school in private schools and the monthly family income was over R$9,000.00 in 69.9% of the students. The majority (84.4%) were involved in academic leagues; only a few (33.5%) did extracurricular internships or participated in some scientific research (25.7%). Choosing a medical specialty mostly occurred during the internship (37.4%) and most of the rejections occurred between the 2nd and 4th year of the course (39.1%). We highlight the number of students (21.2%) that already enters the school with a defined specialty. Most specialties chosen were pediatrics (16.2%) and surgery (14%) and the most rejected was also pediatrics (37.4%) and surgery (31.8%). The main factors identified as choice influences are: aptitude, work performance, satisfactory training in the specialty field and autonomy. When asked where they intended to practice their profession, they answered as follows: in a private office (79.9%), private hospital (73.7%) and public hospital (66.5%). Most students (52%) think they will work between 49 and 60 hours per week, with 3 different employers (50.8%); making more than R$20,000.00 (47.5%) after five years of practice. The majority (86%) imagine themselves working in shifts, on an average of 14.5 years. 82.7% of the students stated that at no point in their medical course, they had information on labor laws and 78.8% denied having received information about the labor market. 98.3% of the students would like the schools to offer more information on the medical specialties, labor market and labor laws. Conclusion: The medical student chooses his specialty for several factors, but he does not know the labor market. The school does not prepare graduates for the effective insertion in the professional world.